Optimalisasi Kinerja Bumdesma “Alaska” Kecamatan Kabuh melalui Pembuatan SOP MSDM - Pratiwi Tri Rahayu; M Yusuf Azwar Anas (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2024)
This research represents a Community Service aimed at enhancing human resource management (HRM) in the Village-Owned Enterprises (Bumdesma) through the creation of Standard Operating Procedures (SOP). Fieldwork Practice (PKL) was conducted with a focus on applying theoretical knowledge of students to real-world contexts. The research stages included organizational needs analysis, active participation in surveys and interviews with employees, and the development of structured SOP. The results of analysis and surveys served as a basis for designing SOP, with careful validation and intensive consultation with stakeholders in Bumdesma. Internal stakeholders, including students, engaged in practical testing and simulation of SOP implementation before official adoption. Students acted as change agents, bringing innovative insights to enrich the SOP development process